STUDI EKSPERIMENTAL PENGARUH KECEPATAN ALIRAN MASUK, SPLIT – RATIO DAN DIAMETER VORTEX FINDER TERHADAP UNJUK KERJA LIQUIDLIQUID CYLINDRICAL CYCLONE (LLCC) SEPARATOR - Irfan Aditya Dharma; Adhika Widyaparaga; Alim Yuandia (Teknoin, 2018)
The large number of ports in Indonesia generate a lot of waste oil that contaminate the ocean around the port. However, the pollution prevention is not supported by a good facility. Hydrocyclone separator can be used as an alternative to supporting conventional separataor technologies such as vessel type separator or gravitational based separator to prevent the waste oil pollution. The purpuse of this study is to determine the effect of split ratio, inlet mixture velocity, and vortex finder diameter on the performance of the liquid-liquid cylindrical cyclone (LLCC). Oil (Kerosene) and water were selected as the working fluid and a red color (dye) was given to the oil to enable visualization . Performance of LLCC determined from watercut that produced from separation process. The examined inlet mixture velocity are 0.7 m/s, 0.9 m/s and 1.1 m/s with split-ratio 5%, 15%, 30%, 45%, 60%, 75% and 90%. . All of them are tested with vortex finders that have diameters 18 mm, 22 mm and 27 mm with 0 mm depth. The oil volume fraction inlet is kept constant at 25%. The result showed that LLCC was capable to separating oil-water mixture and produced watercut on underflow reaches 100%. The increasing of split-ratio will increase the watercut until reached the maximum value for all diameter of vortex finder. The condition when the oil content begin to move to the underflow on certain split-ratio is called oil drag. The split-ratio that used before oil drag occurs is called Optimum Split Ratio (OSR). LLCC should operated on OSR to obtain the best performance. The OSR is shifted to the higher split-ratio for higher inlet mixture velocity. The increasing of vortex finder diameter did not change LLCC performance significantly.